2009
DOI: 10.1007/s11096-009-9311-2
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of patient satisfaction with community pharmacy services: a review

Abstract: This review found that patient satisfaction has been measured within the community pharmacy context to a certain degree. Further research is needed to develop and test instruments based on theoretical frameworks, to test satisfaction pre and post hoc and in well designed randomized controlled trials and to measure changes in satisfaction over time. Novel approaches involving an understanding of expectations and preferences of patients and matching these to the services provided also need to be explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
143
1
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(161 citation statements)
references
References 48 publications
12
143
1
5
Order By: Relevance
“…9 Although a variety of instruments have been developed to measure customer satisfaction with pharmacies/pharmacists (see 10,[11][12][13] ), these instruments do not provide an understanding of customer expectations in relation to the actual services provided. 14 An analysis of the pharmacy staffs' perspective could shed light on this issue if we consider that the difference between consumer expectations of what constitutes good service quality and the pharmacy staffs' understanding of these expectations or their preparedness and ability to meet them determines the pharmacy's actual service quality. 15 In the marketing literature, one of the key models that has endeavoured to explain the discrepancy between consumer expectations and perceptions of service quality is the 'Conceptual Model of Service Quality' developed by Zeithaml, Berry, & Parasuraman.…”
Section: Introductionmentioning
confidence: 99%
“…9 Although a variety of instruments have been developed to measure customer satisfaction with pharmacies/pharmacists (see 10,[11][12][13] ), these instruments do not provide an understanding of customer expectations in relation to the actual services provided. 14 An analysis of the pharmacy staffs' perspective could shed light on this issue if we consider that the difference between consumer expectations of what constitutes good service quality and the pharmacy staffs' understanding of these expectations or their preparedness and ability to meet them determines the pharmacy's actual service quality. 15 In the marketing literature, one of the key models that has endeavoured to explain the discrepancy between consumer expectations and perceptions of service quality is the 'Conceptual Model of Service Quality' developed by Zeithaml, Berry, & Parasuraman.…”
Section: Introductionmentioning
confidence: 99%
“…Inefficient waiting times can invite patients' dissatisfaction with a health service obtained from a pharmacy unit patients will assume poor quality of health [17][18][19][20][21][22] stating that the quality of pharmacy unit services has a positive and significant effect on patient satisfaction. Khudair and Raza [17] identified that the rate of service, officer attitudes, drug information, and location are factors of pharmaceutical service that has a positive and significant effect on patient satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…It can determine the sustainability of a healthcare service (Panvelkar et al, 2009), as well as reflecting the influence of pharmacy services on patients' lives. However, owing to its subjective nature, it is difficult to evaluate and it is not a structure or process measure (Gourley et al, 2001).…”
Section: Literature Reviewmentioning
confidence: 99%